Antibacterial activity of palm leaf extract against Propionibacterium acnes and Staphylococcus aureus - Harmileni, Harmileni; Hidayani, Tengku Rachmi; Chiuman, Linda; Marfitania, Taranipa (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Acne vulgaris is the most common skin disorder in adults and young adults. The growth of acne is caused by many factors, including excess sebum secretion and changes in microbial flora, mainly the colonization of Propionibacterium acnes and Staphylococcus aureus. This study aimed to determine the anti-bacterial activity of palm leaf extract against Propionibacterium acnes and Staphylococcus aureus. The research procedure includes palm leaf extraction and anti-bacterial tests. Palm leaf extraction was carried out using ultrasonication, while the anti-bacterial test was carried out using disc diffusion. The palm leaf extract obtained was diluted to 10, 20, 30, 50, and 50%, and each variation of this concentration was tested for anti-bacterial activity. The results of the anti-bacterial test showed that all palm leaf extract samples from 10% to 50% concentration could inhibit the growth of P. acnes and S. aureus bacteria. The 50% extract of ultrasonicated palm leaves had the largest inhibition zone diameter of 13.8 mm for P. acnes bacteria and 10.1 for S. aureus bacteria. From the results of this study, palm leaf extract has the potential to be used as a product for the prevention or treatment of acne vulgaris.